The use of mouthguards and related factors among basketball players in Indonesia - Herry Novrinda; Putri Tianda Lambe; Risqa Rina Darwita; Jae-Young Lee (BMC, 2023)
Abstract Background Basketball is a sport with a higher injury rate. Regardless, few basketball players use mouthguards, which predisposes them to injuries. The use of mouthguards (UoM) could be related to several factors. This study aims to identify factors associated with UoM and to construct a model from the factors among basketball players in Indonesia. Methods Through convenience sampling, a total of 286 among basketball players in Indonesia was included in this cross-sectional study. These participants filled out online a modified questionnaires regarding demographic and several factors related to UoM. The data was analyzed using chi-square test, independent-sample t-test, binary logistic regression, and structural equation modeling (SEM). Results There were 286 players. 127 of them were males and 159 were females. Of them, 86 (30.1%) used mouthguards. Age, duration (in year), and weekly practicing basketball (in hour) were all significantly different between mouthguards users and non-users with (p = 0.005, p = 0.036 and p = 0.035), respectively. The UoM was significantly associated with level of awareness, injury experience, social support, and oral health professional (OHP) support with (p = 0.002, p < 0.001, p < 0.001 and p < 0.001), respectively. This result was also supported by a variety of variables' ORs, which range from 1.28 to 5.97. The coefficient of determination (R2) was 0.27. Conclusions The UoM among basketball players in Indonesia was related to several factors, including the level of knowledge, level of awareness, duration of basketball career, injury experiences, social support, and oral health professionals' support which was constructed to propose a model. The model could explain 27% of the relationship between variables and UoM among Indonesian basketball players. This model will be useful for more comprehensive initiatives to promote oral health. It might be applicable for other countries as well as other sports communities / physical activities.